Indole-3-carbinol ameliorated the isoproterenol-induced myocardial infarction via multimodal mechanisms in Wistar rats - Ramakrishna K.; Krishnamurthy S. (My University, 2025)
The present study investigated the cardioprotection of Indole-3-carbinol on isoproterenol (ISO)-induced myocardial infarction in Wistar rats. I3C treatment significantly reduced the prolongation of the QRS complex, QT interval, and ST-segment elevation. I3C was also able to normalise blood pressure (SBP, DBP, and MAP) and HR. I3C significantly decreased heart weight, cardiac troponin I (cTn I), CK-MB, LDH, AST and ALT. I3C ameliorated acute hyperglycaemia, hyperlipidemia, and myocardial infarction (%) in ISO rats. I3C treatment significantly elevated the antioxidant enzymes like SOD, CAT, and GSH and attenuated the MDA levels. I3C reduced the inflammatory cytokines (TNF-α and IL-6) and increased the anti-inflammatory cytokine 1 L-10. Furthermore, I3C significantly recovered myocardial structure by inhibiting neutrophil infiltration and oedema. Moreover, I3C attenuated apoptotic markers (cytochrome C, caspase 9 and caspase 3). Consequently, I3C restored cardiac function in MI rats by alleviating oxidative stress, inflammation, and apoptosis, and I3C could be used to treat myocardial infarction. © 2022 Informa UK Limited, trading as Taylor & Francis Group.